STRATEGI PENGELOLAAN KERETA API DALAM MENUJU PELAYANAN YANG BERKUALITAS (Studi Kasus Pada Kereta Api Prameks Solo – Yogyakarta di Stasiun Purwosari) - Natasya Ayu Intan (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to determine the strategy to improve service quality and to determine the management quality strategy scenario on the Prameks Solo Train. This research is quantitative descriptive. The population is all passengers of the Prameks Solo Train. The number of samples used by Sugiyono's guidelines, amounting to 50 respondents, the sample was taken by convenience sampling. The data analysis technique used in this study was Analytical Hierarchy Process (AHP), with Expert Choice 11. The concluded of this researched is that accessibility is the strategy chosen to improve railway management, the scenario needed is consolidation (included in the accessibility criteria) , increased capabilities (included in the mobility criteria), innovation, and world class (included in the reliability criteria). Keywords : Accessibility, Mobility, Reliability.